Resonating Voices - Waves of Sound and Spirit in a Palestinian Musician's Quest for Identity and Freedom - Alsadi, Richard (Taideyliopiston Sibelius-Akatemia, 2025)
This thesis emerges as an exploration of the multifaceted nature of music, identity, and the enduring spirit of a people living through profound challenges. Based on autoethnographic reflection, it provides an introspective exploration of how sound becomes a vessel for presence, a mirror for resilience, and a space for transformation. Through music, this inquiry seeks not merely to articulate personal narratives but to connect them with the common pulse of collective memory—a memory influenced by the persistent realities of displacement and the yearning for freedom that Palestinians, no matter where they are in the world, experience. At the heart of this research lie three case studies that illuminate the potential of music: Sonic Exile, where traditional Arabic modalities and experimental soundscapes dissolve into a single, resonating voice; Echoes from Bethlehem, an improvisational encounter with Palestinian Nay master Faris Ishaq that brings forth a meditative state of being wholly present in sound and spirit; and the work of the Amwaj Choir, where human voice rises above cultural and physical confines, embodying a living, enduring presence. The findings suggest that music is not a static act but a living practice—an unfolding dialogue between tradition and innovation, self and other, silence and sound. Improvisation, as a way of being, becomes a method of both reflection and resistance, enabling a deeper connection to the present moment while engaging with the complexity of the past. The research reveals music’s profound capacity to heal, to resist, and to imagine new pathways for freedom and belonging. Rather than offering definitive conclusions, this thesis extends invitations: to listen, witness, and remain open to the spaces where sound and silence meet, where identity and memory evolve, and where the human spirit, despite all, continues to create and endure.
Keywords: Palestinian Art; Autoethnography; Palestinian Identity; Richard Hanna Jeries Alsadi; musiikki; palestiinalaiset; identiteetti; Palestiina; ääni (fysikaaliset ilmiöt); kulttuuri-identiteetti; lyriikka; hiljaisuus; Global Music